The language of shame: exploring the relationship between vulnerability and flow in teachers' professional lives - Crowe-Stover, Kayla R., author; O'Donnell Allen, Cindy, advisor; Mallette, Dawn, committee member; Reid, Louann, committee member (Colorado State University. Libraries, 2021)
Social emotional intelligence (SEI) strategies and curricula have been developed for over a decade, but the impact of incorporating SEI into education has only recently begun to surface. The majority of research conducted incorporating SEI into the classroom focuses primarily on student impact, whereas, little to no research has been done on how these strategies can be incorporated into professional development and educator sustainability. This study looks specifically at how addressing the emotional complexities of shame and vulnerability, experienced within the teaching profession, is connected to whether or not educators can reach flow state within their classroom. By comparing secondary English teachers' experiences to those of teachers in other secondary disciplines through a survey, narrative journals, and focus group interviews, this study uses grounded theory to investigate how English teachers uniquely experience shame, vulnerability, and flow within their career. Implications from this study may help open up professional dialogue around shared experiences of shame and vulnerability in small teaching communities, as well as helping educators consider implementing strategies that encourage flow within classrooms.
Keywords: flow; social-emotional; vulnerability; shame; English; teaching